N170 Tuning in Chinese: Logographic Characters and Phonetic Pinyin Script. (2nd September 2016) - Qin, Rui; Maurits, Natasha; Maassen, Ben
ABSTRACT: In alphabetic languages, print consistently elicits enhanced, left-lateralized N170 responses in the event-related potential compared to control stimuli. In the current study, we adopted a cross-linguistic design to investigate N170 tuning to logographic Chinese and to pinyin, an auxiliary phonetic system in Chinese. The results demonstrated that logographic characters elicit a left-lateralized print-tuning effect in Chinese readers only. Crucially, the observed tuning effect is clearly driven by script familiarity, rather than by differences in visual features between print and control stimuli. This can be concluded because Dutch participants who viewed the same set of stimuli showed a bilateral topography instead. For pinyin, the left-hemispheric modulation was absent in both language groups, presumably because long strings of pinyin are unfamiliar to both groups. Because grapheme-to-phoneme conversion does not exist in logographic Chinese, our results tend to suggest a visual familiarity rather than a grapheme-to-phoneme mapping account of the print N170.